Market research to determine the viability of the online christian bookstore “The wisdom door” (2015)
This market research investigated the viability to create an online Christian bookstore with English contents for the Christian community in Colombia. Our main purposes were to determine the feasibility of creating this bookshop that we called The Wisdom Door and to identify the possible contents that the Christian believers would like to find in English. Based on a qualitative-exploratory research, we applied as instruments for the data collection, 100 surveys and two focus group with 36 people of the Christian community at the church Manantial de Vida in Bogota to response the research questions. Through the data analysis were established four categories with some subdivisions with the participants’ opinions that revealed that there is a high interest in the Christian believers for the bookstore proposed and we found that The Wisdom Door must to take into account a variety of contents divided in sections, material and topics, to satisfy all the desires and expectations that the potential customers have with the online Christian bookshop in English.